2019
DOI: 10.1111/nep.13564
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous interstitial nephritis on renal biopsy in human immunodeficiency virus positive patients: Prevalence and causes in Cape Town, South Africa

Abstract: South Africa continues to be burdened by human immunodeficiency virus (HIV) and tuberculosis (TB). In Cape Town, the epidemic of HIV‐TB co‐infection is as high as 70%. Granulomatous interstitial nephritis (GIN) has increased in frequency on renal biopsy. This study aimed to determine GIN prevalence and causes in HIV‐positive patients as well as renal outcomes, patient survival and associated factors. This observational cohort study reviewed HIV‐positive renal biopsies for GIN from 2005 to 2012. Causes of GIN (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Timely diagnosis and early treatment of tuberculosis is associated with more favorable outcomes (42). GIN due to tuberculosis is even more common among subjects infected with HIV, and is associated with increased mortality in that case (45). None of our cases were HIVpositive.…”
Section: Discussionmentioning
confidence: 53%
“…Timely diagnosis and early treatment of tuberculosis is associated with more favorable outcomes (42). GIN due to tuberculosis is even more common among subjects infected with HIV, and is associated with increased mortality in that case (45). None of our cases were HIVpositive.…”
Section: Discussionmentioning
confidence: 53%
“…The substantially higher proportion of cases with TID in our series may reflect the exceptionally high prevalence of TB (42%), which can result in granulomatous interstitial nephritis in the kidney, TB drug-induced interstitial nephritis, or ATI from kidney hypoperfusion in those with severe systemic illness. 25 , 26 Furthermore, the greater degree of immunodeficiency in our patients may have resulted in increased susceptibility to other infections and increased exposure to nephrotoxic agents. Of note, about half of the patients with HIV/TB had initiated ART within 3 months of kidney biopsy, raising the possibility that some kidney pathology may have been the result of immune reconstitution inflammatory syndrome in the kidney.…”
Section: Discussionmentioning
confidence: 95%
“…The study confirmed known associations with HIV infection, hypertension, and diabetes 2,30,31 , but one third of participants with CKD had none of these risk factors. Potential contextspecific risk for kidney disease not accounted for in this study include endemic malaria, endemic genitourinary schistosomiasis, genitourinary tuberculosis, ingestion of traditional and overthe-counter medicines, and environmental exposures such as agricultural pesticides and heavy metal toxins [32][33][34] . Such exposures might result in repeated bouts of acute, or acute-on-chronic kidney injury, or comprise the "second hit" needed for APOL1-induced kidney injury.…”
Section: Discussionmentioning
confidence: 99%